2021
DOI: 10.3389/fnut.2021.708069
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of Heavy Metals and Glyphosate in Urine and Hair Before and After Long-Term Fasting in Humans

Abstract: Background: Dietary exposure to environmental pollutants in humans is an important public health concern. While long-term fasting interrupts the dietary exposure to these substances, fat mobilization as an energy source may also release bioaccumulated substances. This was, to our knowledge, only investigated in obese people decades ago. This study explored the effects of 10-days fasting on the excretion of heavy metals and glyphosate.Methods: Urinary levels of arsenic, chromium, cobalt, lead, nickel, mercury a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Creatinine adjustment is more commonly used for organic compounds, such as pesticides, where the goal is to account for variations in urine dilution and correct for differences in excretion rates due to differences in muscle mass [ 25 ]. However, creatinine adjustment may not be necessary or relevant for HM/MTs, as their excretion rates are less influenced by muscle mass and more related to other factors such as exposure levels [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Creatinine adjustment is more commonly used for organic compounds, such as pesticides, where the goal is to account for variations in urine dilution and correct for differences in excretion rates due to differences in muscle mass [ 25 ]. However, creatinine adjustment may not be necessary or relevant for HM/MTs, as their excretion rates are less influenced by muscle mass and more related to other factors such as exposure levels [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous recent studies have reported using urine and hair analysis to determine heavy metal concentrations and signs of cell injury [10,70,71]. To our knowledge, there were limited occupational-related studies in metal intoxication using laboratory experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Blood and urine are the most useful matrixes for metal bio-monitoring. Urinary and blood levels of trace elements reflected short-term and ongoing exposures respectively and their urinary levels mainly reflect their exposures in last few days [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%